Chemical Exchange Saturation Transfer for Pancreatic Ductal Adenocarcinoma Evaluation. Issue 5 (19th May 2022) - Wang, Lixia; Zhou, Zhengwei; Gaddam, Srinivas; Wang, Nan; Xie, Yibin; Deng, Zixin; Fan, Zhaoyang; Christodoulou, Anthony G.; Han, Fei; Lo, Simon K.; Wachsman, Ashley M.; Hendifar, Andrew E.; et al.
Abstract : Objectives: The aims of the study are to evaluate the feasibility of using pH-sensitive magnetic resonance imaging, chemical exchange saturation transfer (CEST) in pancreatic imaging and to differentiate pancreatic ductal adenocarcinoma (PDAC) with the nontumor pancreas (upstream and downstream) and normal control pancreas. Methods: Sixteen CEST images with PDAC and 12 CEST images with normal volunteers were acquired and magnetization transfer ratio with asymmetric analysis were measured in areas of PDAC, upstream, downstream, and normal control pancreas. One-way analysis of variance and receiver operating characteristic curve were used to differentiate tumor from nontumor pancreas. Results: Areas with PDAC showed higher signal intensity than upstream and downstream on CEST images. The mean (standard deviation) values of magnetization transfer ratio with asymmetric analysis were 0.015 (0.034), −0.044 (0.030), −0.019 (0.027), and −0.037 (0.031), respectively, in PDAC area, upstream, downstream, and nontumor area in patient group and −0.008 (0.024) in normal pancreas. Significant differences were found between PDAC and upstream ( P < 0.001), between upstream and normal pancreas ( P = 0.04). Area under curve is 0.857 in differentiating PDAC with nontumor pancreas. Conclusions: pH-sensitive CEST MRI is feasible in pancreatic imaging and can be used to differentiate PDAC from nontumor pancreas. This provides a novel metabolic imaging method in PDAC.